The Role of Undergraduate Alumni of Madrasah Ibtidaiyah Teacher Education in Strengthening Communication Networks and Improving Learning Quality through Parenting Class Activities - Amik Nadziroh; M. Romadlon Habibullah; Shofi Chofiatun Nisa; Ridaul Bariroh (Madrosatuna: Journal of Islamic Elementary School, 2020)
This research purpose to explore the role of graduated of the Madrasah Ibtidaiyah Teacher Education in strengthening communication networks and improving the quality of learning through Parenting Class activities. The focus of the research article is how the approach, implementation and evaluation applied by the alumni in strengthening communication networks and improving the quality of learning through Parenting Class activities?. The method used in this research is a qualitative method whose data is carried out through field practice from 2012 to 2019 using Baumrind's theory, a theory that purpose to explore and attempt to find new theori so that in Islam many of the exemplary concepts in each Parenting Class activity mentioned. The results of the approach by utilizing IT, alumni association forums, alumi annual programs, and establishing a regeneration system. Implementation of activities is the establishment of good alumni, by exchanging idea on improving the quality of education through annual programs and IT media. Meanwhile, parenting class activities useful in achiev the vision and mission of education in which these activities open the fabric of cooperation and transparent systems in educating between teachers and guardians of students, guardians of students with the community, the community with teachers and impacting on the quality of education and certainly constituting strategic management in activities classroom learning.